Identification of genes differentially regulated by vitamin D deficiency that alter lung pathophysiology and inflammation in allergic airways disease - Foong, X.; Bosco, A.; Troy, N.; Gorman, S.; Hart, P.; Kicic, Anthony; Zosky, G. (2016)
© 2016 the American Physiological Society. Vitamin D deficiency is associated with asthma risk. Vitamin D deficiency may enhance the inflammatory response, and we have previously shown that airway remodeling and airway hyperresponsiveness is increased in vitamin D-deficient mice. In thi s study, we hypothesize that vitamin D deficiency would exacerbate house dust mite (HDM)-induced inflammation and alterations in lung structure and function. A BALB/c mouse model of vitamin D deficiency was established by dietary manipulation. Responsiveness to methacholine, airway smooth muscle (ASM) mass, mucus cell metaplasia, lung and airway inflammation, and cytokines in bronchoalveolar lavage (BAL) fluid were assessed. Gene expression patterns in mouse lung samples were profiled by RNA-Seq. HDM exposure increased inflammation and inflammatory cytokines in BAL, baseline airway resistance, tissue elastance, and ASM mass. Vitamin D deficiency enhanced the HDM-induced influx of lymphocytes into BAL, ameliorated the HDM-induced increase in ASM mass, and protected against the HDM-induced increase in baseline airway resistance. RNA-Seq identified nine genes that were differentially regulated by vitamin D deficiency in the lungs of HDM-treated mice. Immunohistochemical staining confirmed that protein expression of midline 1 (MID1) and adrenomedullin was differentially regulated such that they promoted inflammation, while hypoxia-inducible lipid dropletassociated, which is associated with ASM remodeling, was downregulated. Protein expression studies in human bronchial epithelial cells also showed that addition of vitamin D decreased MID1 expression. Differential regulation of these genes by vitamin D deficiency could determine lung inflammation and pathophysiology and suggest that the effect of vitamin D deficiency on HDM-induced allergic airways disease is complex.